2009
DOI: 10.1021/ma901013q
|View full text |Cite
|
Sign up to set email alerts
|

SANS and SLS Studies on Tetra-Arm PEG Gels in As-Prepared and Swollen States

Abstract: A series of model networks consisting of polyethylene glycol (PEG), tetra-PEG gels, have been prepared and their structure and dynamics have been investigated by small-angle neutron scattering (SANS) and static light scattering (SLS). The Tetra-PEG gels were prepared by cross-end coupling of two types of tetra-arm PEG macromers with molecular weights, M w , of (5 to 40) Â 10 3 g/mol. In the SANS regime, the structure factors of both as-prepared and swollen gels can be represented by Ornstein-Zernike-type scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
286
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(312 citation statements)
references
References 49 publications
26
286
0
Order By: Relevance
“…Figure 22 is a master plot of SANS curves for Tetra-PEG gels with various molecular weights, that is, -5K, -10K, -20K and -40K, prepared at various polymer concentrations, f 0 . 93 All of the SANS intensity functions could be superimposed with the reduced variables I(q)/ (f 0 x 2 ) and qx. For qx X10 À1 , the scattering functions fall onto a single master curve given by an Ornstein-Zernike function: 86,93 IðqÞ…”
Section: High-performance Polymer Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 22 is a master plot of SANS curves for Tetra-PEG gels with various molecular weights, that is, -5K, -10K, -20K and -40K, prepared at various polymer concentrations, f 0 . 93 All of the SANS intensity functions could be superimposed with the reduced variables I(q)/ (f 0 x 2 ) and qx. For qx X10 À1 , the scattering functions fall onto a single master curve given by an Ornstein-Zernike function: 86,93 IðqÞ…”
Section: High-performance Polymer Gelsmentioning
confidence: 99%
“…93 All of the SANS intensity functions could be superimposed with the reduced variables I(q)/ (f 0 x 2 ) and qx. For qx X10 À1 , the scattering functions fall onto a single master curve given by an Ornstein-Zernike function: 86,93 IðqÞ…”
Section: High-performance Polymer Gelsmentioning
confidence: 99%
“…To monitor gel dissolution, a trace amount of absorbing and/or fluorescent "erosion" probe was covalently attached by a stable linker to CO residues before hydrogel formation (19). Although we have not studied mechanical or structural properties of these gels, analogous Tetra-PEG gels have been intensively studied and shown to possess near-ideal homogeneous polymer network properties with minimal defects (8,9,20). In another format (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was our desire to develop a system in which we could keep gel properties largely constant, and achieve different degradation rates by modifying the rate of gel scaffold cleavage. In the present work, we tether drugs or drug surrogates to large-pore hydrogels prepared from two multi-arm PEG macromonomers using β-eliminative linkers that cleave at desired rates of drug release; similar β-eliminative linkers having slower cleavage rates are used to cross-link four arms of each macromonomer to form Tetra-PEG gels (8,9). In this manner, either or both cleavage rates can be tuned to coordinate drug release and gel degradation without introducing major structural differences in the gels.…”
mentioning
confidence: 99%
“…Tetra-PEG gels can be well fitted to available theoretical scattering functions (the Ornstein-Zernike function), and no observable excess scattering appears in the small-angle neutron scattering results. 46 Young's modulus of tetra-PEG gels is proportionally correlated to polymer volume fractions, indicating the absence of entanglements in the network. 47 It has been observed that the compressive strength of tetra-PEG gels is on the order of a few to tens of MPa for a 120 mg ml À1 gel made from a macromer with M w ¼10 000.…”
Section: Tetra-peg Gelsmentioning
confidence: 99%